Applied Behavior Modification Techniques for Increasing Assertiveness in Persons with Intellectual Disability - Andayani, Rini Hartini Rind; Sofiani, Tiara Tri; Herlina, Elin; Suyono, Sinta Yulianti (Global Writing Academica Researching & Publishing, 2025)
This study evaluated the effectiveness of behavior modification techniques to enhance assertiveness in a person with intellectual disability identified as having low assertive behavior. Using a single-subject experimental design A–B–A with quantitative descriptive methods, the intervention targeted measurable deficits identified during baseline assessment. The participant, classified as imbecile and receiving services at Sentra Terpadu Kartini Temanggung, was selected through recommendations from social workers and dormitory supervisors. Two primary techniques modelling and advice giving with instruction were implemented across the intervention phase. Assertive behavior was measured via participatory observation using a Likert scale, focusing on specific skills such as refusal of unwanted physical contact. The intervention emphasized positive support to enable the participant to express feelings and set personal boundaries assertively. Results demonstrated a marked improvement in assertive responses, notably refusal of physical touch, yielding a post-intervention score of 340. Observations indicated the participant could effectively refuse attempts by opposite-sex individuals to touch sensitive body areas. These outcomes suggest that targeted behaviour modification procedures can produce clinically meaningful gains in basic assertiveness among persons with intellectual disabilities. The study contributes empirical evidence for the application of modelling and directive advice in social rehabilitation settings. Implications include the potential adoption of these techniques by practitioners to inform individualized intervention planning and to strengthen foundational assertiveness skills based on assessment-driven priorities.